The effect of positive parenting program on mental health in mothers of children with intellectual disability. (September 2019) - Ashori, Mohammad; Norouzi, Ghasem; Jalil-Abkenar, Seyyedeh Somayyeh
The aim of this research was to examine the effectiveness of positive parenting program (Triple-P) on the mental health of mothers of children with intellectual disability (ID). This study was a quasi-experimental research with pretest, posttest design, and a control group. Thirty-six mothers of students with ID participated in this study and were divided into two groups (intervention group and control group). Each group consisted of 18 participants. The intervention group received a parent training program during 12 sessions, each session lasting for 80 min, while the control group did not receive any special training. Multivariate analysis of covariance test was applied to analyze the obtained data using SPSS software. The results of this study indicated that Triple-P had significant effect on the somatic symptoms, anxiety, depression, social dysfunction, and mental health of mothers of children with ID. As a result, this research emphasized that parenting skills training will improve the mental health of mothers of children with ID, and therefore, planning for Triple-P training is of particular importance.